INNOVATIVE METHODS FOR DEVELOPING STUDENTS’ CREATIVITY IN THE EDUCATIONAL PROCESS (Eureka Journal of Education & Learning Technologies, 2026)
The article presents a model for developing students’ personal-creative competence, which includes goal-oriented, content-technological, organizational-functional, and result-oriented evaluative components. The methods and forms of instruction that stimulate students’ creative thinking and independence are described. The importance of the model’s flexibility and the use of interactive technologies to adapt to changes in the educational environment is emphasized. The research results can be applied to improve teaching methodologies and the training of competitive specialists.
Keywords: Personal-creative competence, pedagogical education, technological approach, student creativity, teaching methods, interactive technologies.